Who Benefits from Faster Public Transit? - Prottoy A. Akbar (Helsinki Graduate School of Economics, 2024)
Lower income commuters are more likely to ride and reside near public transit within cities, but do they also benefit more from faster transit travel? Combining survey data on travel behavior with web-scraped data on counterfactual travel times for millions of trips across 49 large US cities, I estimate a model of travel mode and residential location choice. I characterize the heterogeneity across income groups and cities in commuters' willingness to pay for access to faster transit and the expected increase in transit ridership in response to marginal transit improvements. I find that higher-income transit riders sort more aggressively into the fastest transit routes and are, on average, willing to pay more for faster commutes. Improvements in transit speed are most effective at generating transit ridership and welfare gains where transit is already fast (relative to driving), in cities with a greater share of rail-based transit and where the gains are larger for higher-income commuters. Transit improvements benefit lower-income commuters more where transit is relatively slow, in cities with more bus transit, and where the overall marginal gains are small.
Keywords: R23; R41; 330; travel mode choice; residential location choice; mass transit; public transportation; income sorting